2023
DOI: 10.1007/s42452-023-05328-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure, morphology, magnetism, and magnetocaloric-effect studies of (La1−xPrx)0.7Sr0.3MnO3 nanocrystalline perovskites

Abstract: Single-Phase (La1–xPrx)0.7Sr0.3MnO3 (x = 0.0, 0.2, 0.4, 0.6, 0.8, and 1.0) perovskites were synthesized by the sol–gel method followed by sintering at 700 °C for 5 h. Samples with x = 0.0–0.4 are found to crystallize into rhombohedral structure (R-3c space group) while the ones with x = 0.6–1.0 crystallize into orthorhombic structure (Pbnm space group). The average particle size of the samples was in the range of 21–44 nm. All samples exhibit a ferromagnetic to paramagnetic second-order magnetic phase transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…49 The spin-orbit splitting of the La 3d level (B16.8 eV) was identical for all the compounds and was close to those observed for perovskite samples. [48][49][50][51] The Ba 3d core levels exhibit doublet structures, as shown in Fig. 8c.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 88%
See 1 more Smart Citation
“…49 The spin-orbit splitting of the La 3d level (B16.8 eV) was identical for all the compounds and was close to those observed for perovskite samples. [48][49][50][51] The Ba 3d core levels exhibit doublet structures, as shown in Fig. 8c.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 88%
“…The difference in the binding energy is B11.7 eV, which is close to those observed for perovskite samples. 50 Based on stoichiometry, LBCS compounds have mixed valence Mn 3+ and Mn 4+ , which appear due to the divalent substitution at the A-site. Previous studies indicated that the binding energies near Mn 2p 3/2 for Mn 2 O 3 (641.7 eV) and MnO 2 (642.8 eV) correspond to these specific manganese oxides Mn 3+ and Mn 4+ , respectively.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Both represent the amount of heat available for transfer between the hot and cold sides in one ideal Carnot cycle. 39,47,48…”
Section: Fundamental Aspectsmentioning
confidence: 99%
“…1 Furthermore, many researchers have assumed that δ T FWHM = T 2 − T 1 , where T 2 and T 1 are the normalizations of the value . 47,49…”
Section: Fundamental Aspectsmentioning
confidence: 99%
See 1 more Smart Citation